Implementation of The draivCare App on Maternal Health Services - Yuwono, Dian Kurniasari; Monoarfa, Yustianty; Galenso, Nitro (Poltekkes Kemenkes Palu, 2025)
Background: Banggai Regency government collaborated with a local start-up, Draiv, to develop a health service app specialized for pregnant women, called draivCare. This study aims to evaluate the effect of draivCare utilization on maternal health services. Methods: This is a case-control method to identify the differentiation of ANC services utilization during the pregnancy period between groups. We use secondary data and conducting interview with midwives. A total 39 pregnant women who use draivCare app in their pregnancy were administered to the intervention(case) group, whereas 156 pregnant women who did not use draivCare app in their pregnancy belong to the control group. Antenatal care (ANC) frequency and components were the variables studied using chi-square. Results: The proportion of mother who received the fetal examination and the proportion of mothers who received tetanus toxoid immunization are significantly differ between groups. Despite the barriers such as android-based mobile phone ownership of the mothers, the communication between pregnant women and midwives is quite intense. Conclusion: The implementation of draivCare app has yet to affect pregnant women’s health care quality and quantity significantly. However, the intense communication between pregnant women and midwives shows a potential effect of the app on improving antenatal care.